Pembelajaran Al-Qur’an di MTs Yuppi Musirawas (Analisis Strategi Guru dalam Pembelajaran Tahfidz Al-Qur’an Siswa) - Muhammad Salim (UIN Fatmawati Sukarno Bengkulu, 2022)
The purpose of this study is to describe the teacher’s strategy in learning the Qur’an at MTs YUPPI Musi Rawas, as well as to explain the supporting and inhibiting factors in the learning of Al-Qur’an teachers and students at MTs YUPPI Musi Rawas. This research method is a qualitative research, the data source is obtained from the principal, teachers and students, while the data collection techniques used are observation, interviews and documentation. The results of this study are: first, the implementation of Al-Qur’an learning, MTs YUPPI Musi Rawas has implemented strategies in its learning. This strategy starts from the new school year. The method of delivery in learning uses the sorogan and kalsikal models. Second, supporting factors include: the fulfillment of the number of experienced, creative and active teachers in teaching, high student motivation in learning, activity programs that support the learning of the Qur’an, the availability of learning media, a conducive environment. While the inhibiting factors are: The decline in the quality of teachers in terms of intellect, experience and seniority, Lack of a sense of responsibility and the spirit of educators from teachers, The number of outside teachers is more than teachers in Islamic boarding schools, The decline in students’ enthusiasm for learning, Weakness in the curriculum and learning methodology, lack of operational funds for development.